Digital Media Innovation For Istima' Teaching In Arabic Language Education: Literature Study - Rizka Sari; Anwar Sidik (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
Listening (istima’) is one of the four essential skills in Arabic language learning that plays a crucial role in understanding spoken messages. However, in Indonesia, the teaching of istima’ is still largely conducted using conventional methods, which tend to be monotonous and less effective. Technological advancements have led to various digital media innovations that support more interactive, flexible, and contextual listening instruction. This study aims to identify forms of digital media innovation in istima’ instruction, evaluate their effectiveness, and analyze the supporting and inhibiting factors in their implementation. The method used is a literature review with content analysis techniques. The findings show that media such as animated videos, podcasts, mobile applications, and online platforms can enhance student motivation, participation, and learning outcomes. These innovations also promote flexible, independent, and needs-based learning. However, the effectiveness of digital media depends on content quality, teacher competence, and infrastructure readiness. Therefore, the integration of digital media in istima’ instruction must be pedagogically and strategically designed. This study provides theoretical and practical contributions to the development of modern and 21st-century-relevant Arabic language learning.